2019
DOI: 10.5530/jyp.2019.11.55
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Reverse-phase High-performance Liquid Chromatographic Method for the Quantification of Raltegravir Potassium in Bulk and Dosage Forms

Abstract: Objectives: The aim of this present study is to develop an accurate, precise and linear Reverse-phase High-performance Liquid Chromatographic (RP-HPLC) method for the estimation of raltegravir potassium in the bulk and pharmaceutical dosage form. Methods: The chromatographic system employs a reverse phase shim-pack C 18 column, (150 x 4.6 mm; 5 μ) using the mobile phase acetonitrile: (0.05 M) ammonium acetate buffer, (pH-4 adjusted with glacial acetic acid) in the proportion of 50:50 v/v, delivered at a flow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…(9) Comprehensive data generated with a PDA detector and an MS detector is useful for the correct identification and confirmation of peaks based on spectra and molecular weight. (10) The molecular weight of an unspecified degradation product or peak will be helpful to identify or predict the root cause or source of contamination in the analysis.…”
Section: Significance Of the Proposed Research Work Compared To Publi...mentioning
confidence: 99%
See 1 more Smart Citation
“…(9) Comprehensive data generated with a PDA detector and an MS detector is useful for the correct identification and confirmation of peaks based on spectra and molecular weight. (10) The molecular weight of an unspecified degradation product or peak will be helpful to identify or predict the root cause or source of contamination in the analysis.…”
Section: Significance Of the Proposed Research Work Compared To Publi...mentioning
confidence: 99%
“…Several different techniques have been described in the literature for the estimation of rilpivirine in pharmaceutical and biological samples. A thorough literature review study demonstrated that different analytical techniques were used for the estimation of rilpivirine as a single content using spectrophotometric [4,5], HPTLC [6], HPLC [7][8][9][10], UPLC [11], LC-MS [12], and LC-MS/MS [13][14][15] in different matrixes (bulk, tablets, nanoparticles, saliva, serum, and human plasma). The literature also revealed the number of methods including RP-HPLC [16][17][18][19][20][21][22][23][24][25][26], HPLC-MS/MS [27][28][29][30][31], RP-UPLC [32][33], and UPLC-MS/MS [34][35][36] for the determination of rilpivirine in the presence of other antiretroviral drug molecules.…”
Section: Introductionmentioning
confidence: 99%